Beyond the Algorithm. Ethical and aesthetic challenges of AI in music (Itinera, 2024)
This paper explores the intersection of music and artificial intelligence (AI). The document discusses significant projects like Sony's Flow Machines and AIVA, highlighting how AI is utilized in the musical domain as an assistive tool (e.g., in activities like editing), an analytical instrument (for understanding musical language, for instance, in musicological research), for profiling (for targeting purposes and beyond), and for generating music.The paper lists several open questions, such as issues related to the attribution of works, the originality of AI-generated music and copyright law and it also delves into the legal and ethical implications, particularly regarding copyright and the potential for AI to commit plagiarism or create derivative works.Key challenges and considerations in AI-generated music are addressed, including autonomy,  creativity, and intentionality. While AI's capacity for creativity is still evolving, the need for human intervention in training and refining AI outputs is still crucial. The intentionality behind AI-created music and the integration of human values are critical in ensuring that the produced music is meaningful and resonates with human audiences. Finally, this study examines whether AI can be considered a creative entity or if it functions merely as an advanced tool for human composers, analyzing the aesthetic and functional transformations brought about by AI in the realm of music creation.
Keywords: Generative Music, Autonomy, Creativity, Intentionality